2017
DOI: 10.1080/21505594.2017.1328343
|View full text |Cite
|
Sign up to set email alerts
|

TheAspergillus fumigatusfarnesyltransferase β-subunit, RamA, mediates growth, virulence, and antifungal susceptibility

Abstract: Post-translational prenylation mechanisms, including farnesylation and geranylgeranylation, mediate both subcellular localization and protein-protein interaction in eukaryotes. The prenyltransferase complex is an αβ heterodimer in which the essential α-subunit is common to both the farnesyltransferase and the geranylgeranyltransferase type-I enzymes. The β-subunit is unique to each enzyme. Farnesyltransferase activity is an important mediator of protein localization and subsequent signaling for multiple protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…AlcC has been identified as the primary hypoxia-responsive ADH in A. fumigatus, with a potential role in pathogenesis, 51 while farnesyltransferase has a role in signalling and also contributes to disease. 52 Further investigation could elucidate the effect of DTG on the functionality of these proteins in A. fumigatus. Pre-incubation of DTG with excess Zn 2+ abrogated this effect, most likely through formation of Zn(DTG) complexes prior to addition to protein lysates, leading to reduced levels of protein aggregation.…”
Section: +mentioning
confidence: 99%
“…AlcC has been identified as the primary hypoxia-responsive ADH in A. fumigatus, with a potential role in pathogenesis, 51 while farnesyltransferase has a role in signalling and also contributes to disease. 52 Further investigation could elucidate the effect of DTG on the functionality of these proteins in A. fumigatus. Pre-incubation of DTG with excess Zn 2+ abrogated this effect, most likely through formation of Zn(DTG) complexes prior to addition to protein lysates, leading to reduced levels of protein aggregation.…”
Section: +mentioning
confidence: 99%
“…In addition, we have previously shown that Ras signalling is required for cell wall stability in A . fumigatus (Fortwendel et al, ; Norton, Al Abdallah, Hill, Lovingood, & Fortwendel, ). To determine potential involvement of A .…”
Section: Resultsmentioning
confidence: 99%
“…All animal experiments were done according to protocols approved by the University of Tennessee Institutional Animal Care and Use Committee. For the virulence studies using A. fumigatus strains, six-week-old female CF-1 mice (Harlan Laboratories) were immunosuppressed using two different protocols previously described [33]. For both the non-neutropenic and neutropenic models of invasive aspergillosis, mice were subcutaneously injected with 40 mg/kg of triamcinolone acetonide one day prior to infection.…”
Section: Virulence Studiesmentioning
confidence: 99%
“…CDC43, which is the β-subunit of GGTase-I, is essential in S. cerevisiae [26], and mediates morphogenesis in C. albicans [31] and thermotolerance, morphology, and virulence in C. neoformans [32]. Recently, we characterized the β-subunit of the farnesyltransferase complex (RamA) in Aspergillus fumigatus and demonstrated that ramA null mutants display attenuated virulence, accompanied by growth defects and decreased conidial viability [33]. In this mutant, localization of RasA was only partially impaired, suggesting that lack of Ras farnesylation could be compensated by GGTase-I activity.…”
Section: Introductionmentioning
confidence: 99%